Copper and Antimicrobial Residues in the Liver and Kidney—Antimicrobial Resistance and Cu Tolerance Unrelated in Escherichia coli from Piglets’ Faeces - Maria Manuel Donato; Olga Cardoso; Gabriela Assis; Sara Carolina Henriques; Andreia Freitas; Fernando Ramos (Microorganisms)
Antimicrobials, widely used in livestock, have induced the emergence of antimicrobial-resistant bacteria, prompting farmers to explore alternatives like copper. This study aims to determine antimicrobial residues and Cu concentrations in the liver and kidney of piglets and to investigate the correlation between Cu and antimicrobial use and the resistance to Cu and antimicrobials of Escherichia coli isolated from piglets’ faeces. Antimicrobial residues were quantified by UHPLC-ToF-MS; Cu was quantified using FAAS; microbiological methods were used for E. coli isolation, CuSO4 minimal inhibitory concentration (MIC), and antimicrobial susceptibility; and to detect genes, Real-Time PCR was used. Cu concentrations and antimicrobial residues in piglet livers and kidneys revealed no significant differences. Antimicrobial residues were detected in a significant number of livers and kidneys. While Cu concentrations in the liver were within adequate ranges, those in the kidney exceeded the recommended levels. E. coli isolates from piglet faeces exhibited high antimicrobial drug resistance (AMR), with no clear link to Cu exposure. The genes copA, pcoA, and pcoD, associated with Cu tolerance, were predominantly found in isolates with a CuSO4 MIC of 8 mM. Cu was not used excessively, suggesting that Cu did not replace antimicrobials. E. coli was mostly resistant to antimicrobials and it was not possible to demonstrate that Cu was the trigger for this resistance. There was no relationship between Cu tolerance and AMR in E. coli isolates. This study highlights the need for further research on the complex interplay between metals, antimicrobials, and bacterial resistance in livestock, impacting ‘One Health’.